2016
DOI: 10.1159/000441882
|View full text |Cite
|
Sign up to set email alerts
|

Hidden and Neglected: Food Poverty in the Global North - The Case of Germany

Abstract: Although still a powerful economy, Germany faces rising income inequality and food insecurity. Quantitative data show that nutritional poverty in Germany has become a fact, especially for social welfare recipients. This contribution gives an overview and discusses the limits of results from different data sources, such as German food surveys, and addresses how affected population groups are systematically underrepresented. To give a more thorough impression of food insecurity in Germany, the article compares n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…These surveys, along with others conducted in the United Kingdom, Portugal, and Denmark, are based on representative samples [90,94,95,98]. Also proliferating in Europe are studies on the affordability of nutritionally adequate diets [69,71,[102][103][104][105][106]. These studies, which indicate that from 0.3%-3.5% to ∼10% of the population cannot afford a healthy diet, contribute to the evidence that a significant portion of the European population is experiencing financial constraints that impact their ability to eat a healthy diet.…”
Section: Prevalencementioning
confidence: 99%
“…These surveys, along with others conducted in the United Kingdom, Portugal, and Denmark, are based on representative samples [90,94,95,98]. Also proliferating in Europe are studies on the affordability of nutritionally adequate diets [69,71,[102][103][104][105][106]. These studies, which indicate that from 0.3%-3.5% to ∼10% of the population cannot afford a healthy diet, contribute to the evidence that a significant portion of the European population is experiencing financial constraints that impact their ability to eat a healthy diet.…”
Section: Prevalencementioning
confidence: 99%
“…Also proliferating in Europe are studies on the affordability of nutritionally adequate diets [ 69 , 71 , [102] , [103] , [104] , [105] , [106] ]. These studies, which indicate that from 0.3%–3.5% to ∼10% of the population cannot afford a healthy diet, contribute to the evidence that a significant portion of the European population is experiencing financial constraints that impact their ability to eat a healthy diet.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, for example, a study on the effects of the 2007-2009 recession showed that unemployment and food insecurity are strongly correlated (Huang et al, 2016). Evaluations made by the German Socio-Economic Panel (SOEP) show that the share of the household budget spent on food (19.2%) is significantly higher for unemployed people, but the absolute sum of €205 is considerably lower compared to working households (13.7% and 362€) (Pfeiffer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%